1996
DOI: 10.1039/p29960002497
|View full text |Cite
|
Sign up to set email alerts
|

Reduction potentials of flavonoid and model phenoxyl radicals. Which ring in flavonoids is responsible for antioxidant activity?

Abstract: Model phenoxyl and more complex flavonoid radicals were generated by azide radical induced oneelectron oxidation in aqueous solutions. Spectral, acid-base and redox properties of the radicals were investigated by the pulse radiolysis technique. The physicochemical characteristics of the flavonoid radicals closely match those of the ring with the lower reduction potential. In flavonoids which have a 3,s-dihydroxyanisole (catechins), or a 2,4-dihydroxyacetophenone (hesperidin, rutin, quercetin)-like A ring and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
243
0
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(265 citation statements)
references
References 26 publications
16
243
0
6
Order By: Relevance
“…It is known that procyanidins have an elevated antioxidant effect, thereby being highly susceptible to oxidation, probably because they possess ortho-dihydroxyl groups on their structure, providing reaction sites [23]. We hypothesized a change in the procyanidins redox state during exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that procyanidins have an elevated antioxidant effect, thereby being highly susceptible to oxidation, probably because they possess ortho-dihydroxyl groups on their structure, providing reaction sites [23]. We hypothesized a change in the procyanidins redox state during exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to act as chemical defence agents by donating an electron to an oxidant depends critically on the reduction potentials of their radicals. Structure-activity relationship studies of flavonoids have shown that the o-dihydroxy structure in the ring B and the 2,3-double bond in conjugation with the 4-oxo function in the ring C (as in flavones) is essential for effective free radical scavenging activity [6]. The presence of a 3-hydroxyl group in the heterocyclic ring also increases the radical scavenging activity while additional hydroxyl groups at positions 5 and 7 of the ring A appear to be less important [7].…”
Section: Introductionmentioning
confidence: 99%
“…В качестве доказательства приведенных за-кономерностей отметим, что при использовании циклической вольтметрии флавоноиды лютеолин и кверцетин, содержащие в молекуле катехольный фрагмент, оказались более мощными ингибитора-ми реакции Фентона, чем байцилеин и нарингенин, в структуре которых этот фрагмент отсутствует [26]. Ведущая роль в связывании железа катехольной группы у кольца B в сравнении с кольцом А была под-тверждена и другими исследователями [14,19,43]. Роль гидроксилов в 3-м и 5-м положениях в ком-плексе с 4-оксогруппой в процессе хелатирования железа также была продемонстрирована в экспери-менте [47].…”
unclassified